Animating cuts with on-the-fly re-meshing - GANOVELLI, FABIO; O'SULLIVAN, CAROL ANN (My University, 2001)
The problem of defining a model for deformable objects which allows the user to perform cuts is still open. Generally speaking, the reason is that such a task affects the connectivity and the topology of the mesh, while the assumption that they never change is the basis of most algorithms for both computation of deformation and collision detection. The drawback of approaching this problem as one of cutting based on re-meshing, is that the mesh exhibits a higher density where it has been cut than elsewhere. This paper proposes an on-the-fly tetrahedral simplification scheme to cope with such a fragmentation problem.
PUBLISHED
Keywords: collision detection; virtual surgery